EFFECTS OF BUSERELIN ACETATE ON CONCEPTION RATE IN REPEAT BREEDING DAIRY CATTLE - HAILU, BIRHANU; GEBREKIDAN, BERIHU; ALEMAYEHU, GEZAHIGN; TEKLU, TESHALE (The Indian Journal of Animal Reproduction, 2023)
The aim of the present study was to evaluate the effect buserelin acetate given 12 days post Al anddouble inseminations during estrus period of dairy cattle on improvement of conception rate. Field trial wascarried out on repeat breeding cross breed dairy cows which are lactating and apparently healthy that exhibitsestrus regularly. A total of forty four repeat-breeding cows from twenty herds were selected and assignedrandomly in to two equal groups, A and B: one treated and one control group. Group A (n=22) cattle weretreated intramuscularly with 10 μg buserelin acetate 12 days post Al. Group B (n=22) cattle were inseminatedonce during estrus exhibition with single service and considered as control. Dairy cows were examined forpregnancy after three months through rectal palpation. Pregnancy rates recorded were 55%, and 32% in Aand B respectively. The conception rates of treated group exceed control group by 23% respectively. Treatedgroup showed a significant statistical variation (P
Keywords: Crossbred cattle; Estrus; Buserelin acetate; Pregnancy rates